Prevalence of human papillomavirus type-18 in head and neck cancer among the Chinese population: A PRISMA-compliant meta-analysis. Issue 8 (February 2019) - Yang, Funa; Yin, Yulin; Li, Peng; Zhang, Xiaojun; Chen, Defeng; Liu, Yang; Wang, Jian; Guo, Lanwei
Abstract: Background: China has a high burden of head and neck cancer globally and oncogenic human papillomavirus (HPV) has been hypothesized as a risk factor for head and neck cancer, but research was absent for establishing HPV prevalence in China. We aimed to conduct a meta-analysis to estimate the high-risk HPV-18 prevalence of head and neck cancer in the Chinese population. Methods: This meta-analysis was reported following the guideline of PRISMA. The reports on HPV and head and neck cancer in a Chinese population published between Jan 1, 2006 and May 31, 2018 were retrieved via CNKI/WANFANG/MEDLINE/EMBASE/COCHRANE databases. A random-effect model was used to calculate pooled prevalence and corresponding 95% confidence intervals. Results: A total of 1881 head and neck cancer cases from 19 studies were included in this meta-analysis. Overall, the pooled HPV-18 prevalence among head and neck cancer cases was 6.0% (4.1%–7.9%) in China, 31.2% (13.0%–49.4%) in laryngeal cancer, 7.2% (3.9%–10.5%) in oral cancer and 0.6% (0.0%–1.3%) in oropharyngeal cancer, 18.7% (6.2%–31.2%) in fresh or frozen biopsies and 4.3% (2.5%–6.1%) in paraffin-embedded fixed biopsies, 29.5% (15.6%–43.3%) by E6/E7 region and 3.9% (0.5%–7.4%) by L1 region of HPV gene. The highest HPV-18 prevalence was found in Central China. Conclusions: High prevalence of HPV-18 was found in the samples of Chinese head and neck cancers. Prophylactic HPV-vaccination may reduce the burden of HPV-related head and neck cancer in China.